PERANCANGAN STRATEGI EKSPANSI DAN PERSIAPAN INITIAL PUBLIC OFFERING (IPO) PADA CV KHAWLA ATELIER - Nurlistia Sani; Hendra Lukito (Halu Oleo University, 2025)
This study examines the expansion strategy and preparations for the Initial Public Offering (IPO) of CV Khawla Atelier through a comprehensive approach. Qualitative methods were used to analyze macro-level external factors through PESTEL analysis, identify the business environment through a SWOT Matrix, identify product-market growth opportunities through the Ansoff Matrix approach, and assess IPO readiness through an examination of financial, legal, and governance aspects, as well as corporate structure. Data collection was conducted through semi-structured interviews with the CEO, Production Manager, Finance Manager (internal), the Cooperative and SME Office of Payakumbuh City, and customers (external). Data analysis utilised triangulation techniques—data reduction, data presentation, and conclusion drawing. The research findings emphasise that an in-depth analysis of macro-level external factors, a comprehensive identification of the business environment and product-market growth potential, and an assessment of the current IPO readiness level provide CV Khawla Atelier with a better understanding of how to develop effective expansion strategies and prepare for an IPO more effectively. CV Khawla Atelier needs to optimize the drafting of formal employment contracts and wage structures, implement an inventory management system, optimize digital-based promotion and sales, add casual fashion models while maintaining ethnic and traditional elements for young people, patent its works through intellectual property registration, and improve production management and corporate management to accelerate the company's transformation into a legal entity (PT) as a prerequisite for conducting an IPO. Effective business strategies offer opportunities for the fashion business to grow and gain a competitive edge in the future.